Music therapy in children's palliative care : collaborative family and practitioner voices - Kammin, Victoria; Russell, Julie (Mother of Fraser) (Routledge, 2025)
"Giving voice to the perspectives of children and families with lived experience of children's palliative care, Music Therapy in Children's Palliative Care: Collaborative Family and Practitioner Voices explores the integral role of music therapy and its benefits for supporting child and family wellbeing within a range of children's palliative care settings. This book places the voices of children and families supported by children's palliative care at the centre as they articulate their own experiences of music therapy alongside music therapists to develop theory and practice in this area. Through their unique, collaborative writing approach, contributing authors ensure that both perspectives of the therapeutic relationship - those of the families and the therapists - are represented throughout, offering a comprehensive view of their shared journey. Readers will benefit from learning about how music therapy may offer physical, emotional, social and spiritual support, aiming to enhance quality of life for both children and families. Equality, inclusion and belonging operate at the heart of this book, capturing the diversity of families that use palliative care services. This book is a must read for any music therapist working within a children's palliative care setting. It will also be a compelling text for those with lived experiences, practitioners, educators, students and researchers"-- Provided by publisher.
Keywords: Music therapy for children.; Hospice care.; Palliative treatment.; elektronické knihy; electronic books